2012
DOI: 10.1136/bmjopen-2011-000711
|View full text |Cite|
|
Sign up to set email alerts
|

Feasibility study of geospatial mapping of chronic disease risk to inform public health commissioning

Abstract: ObjectiveTo explore the feasibility of producing small-area geospatial maps of chronic disease risk for use by clinical commissioning groups and public health teams.Study designCross-sectional geospatial analysis using routinely collected general practitioner electronic record data.Sample and settingTower Hamlets, an inner-city district of London, UK, characterised by high socioeconomic and ethnic diversity and high prevalence of non-communicable diseases.MethodsThe authors used type 2 diabetes as an example. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 32 publications
3
48
0
3
Order By: Relevance
“…A correlation of the two poverty measures gave a highly significant relationship of 0.73. Similar findings were shown in Noble et al (2012).…”
Section: Deprivation and Cartographysupporting
confidence: 79%
See 1 more Smart Citation
“…A correlation of the two poverty measures gave a highly significant relationship of 0.73. Similar findings were shown in Noble et al (2012).…”
Section: Deprivation and Cartographysupporting
confidence: 79%
“…Since these landmark studies, maps have been used in public policy research. This has been seen in their use for examining the relationship between poverty and environmental risks (Holton, 2004), health (for example Noble et al, 2012) or just simply the spatial patterning of deprivation in major reports (for example CPAG, 2012). The visual nature of maps means that they are good at raising public awareness due to the improvement in data presentation when compared to other dissemination approaches.…”
Section: Deprivation and Cartographymentioning
confidence: 99%
“…4 Large routine healthcare data sets are uniquely valuable, in that they offer sufficient power to study individual ethnic groups, sex differences, and trends across generations.…”
Section: Resultsmentioning
confidence: 99%
“…For example, maps created by our group in 2012 illustrating 'hot spots' for diabetes risk in Tower Hamlets highlight not only the uniformly elevated risk for South Asian individuals across the borough but also reveal striking similarities to poverty maps created in the late 19th century, with areas of high diabetes risk overlapping areas of high deprivation. 4 An example illustrating the effects of cultural beliefs on health comes from our work evaluating the childhood immunisation arm of a major quality improvement programme involving the formation of GP networks in Tower Hamlets. We found that a borough-wide target of 95% for first mumps, measles, and rubella (MMR) by 2 years of age was achievable.…”
Section: 3mentioning
confidence: 99%
“…The methods have been previously described. 11,12 In summary, a cross-sectional analysis was undertaken in August 2011 of all adults aged 25-79 years without diabetes. Individuals with a Read Code for diabetes were excluded.…”
Section: Methodsmentioning
confidence: 99%